The Relationship between Language Learning Strategies used by Vocational Students and Level of Proficiency (e-Journal of Linguistics, 2020)
The vocational college students instructed by the teacher to used self-directed learning in learning English outside classroom or during theinternship. Due to the requirement of graduation which they should passthe TOEFL test after the internship. The self-directed learning isexercised by managing students’ Language Learning Strategies (LLS)which known could improve language proficiency. Hereby, this studyidentifies: (1) the language learning strategy used by vocational collegelearners based on high and low proficient, (2) the relationship betweenlanguage learning strategy and English proficiency of high proficient,(3) the relationship between language learning strategy and Englishproficiency of high proficient. The participant of this study is 52students of Politeknik Kota Malang which willing to complete theStrategy Inventory of Language Learning (SILL) and done the TOEFLtest. This study employed correlational research design to identify therelationship between variables which is multiple regression analysisemployed in this study. There are six strategies of language learningstrategies by Oxford (1990) as the independent variables (predictors)and English proficiency (criterion) as the dependent variable. The resultshowed that Although, language learning strategy cannotsimultaneously predict the English proficiency of high proficient andlow proficient, compensation strategy reported as high frequently usedby high proficient learners. While metacognitive strategies reportedused by low proficient learners.
Keywords: Language Learning Strategies EFL Learners; English Proficiency of High Proficient; English Proficiency of Low Proficient